The Place of Nailfold Capillaroscopy Among Instrumental Methods for Assessment of Some Peripheral Ischaemic Syndromes in Rheumatology - Lambova Sevdalina N. (Folia Medica, 2016)
Micro- and macrovascular pathology is a frequent finding in a number of common rheumatic diseases. Secondary Raynaud’s phenomenon (RP) is among the most common symptoms in systemic sclerosis and several other systemic autoimmune diseases including a broad differential diagnosis. It should be also differential from other peripheral vascular syndromes such as embolism, thrombosis, etc., some of which lead to clinical manifestation of the blue toe syndrome.